A Review on the Role of Agroecology in Achieving Sustainable Development Goals - Gupta, Shashank (British Journal of Agroecology and Environmental Studies, 2025)
This review explores the role of agroecology in advancing the United Nations Sustainable Development Goals (SDGs), with particular emphasis on food security, environmental sustainability, and social equity. Agroecology, as both a scientific approach and a set of practices, integrates ecological principles into agricultural systems, promoting resilience, resource efficiency, and biodiversity conservation. The review synthesizes existing literature to highlight how agroecological practices contribute to key SDGs, including zero hunger (SDG 2) through enhanced food sovereignty and nutrition, climate action (SDG 13) via mitigation and adaptation strategies, and life on land (SDG 15) through soil health and biodiversity preservation. Moreover, agroecology fosters inclusive rural development and gender equality (SDGs 1, 5, and 10) by empowering smallholder farmers and marginalized groups. While evidence shows that agroecology offers a viable pathway to sustainable and just food systems, challenges such as policy misalignment, limited institutional support, and knowledge gaps hinder its broader adoption. The study concludes that scaling up agroecology requires supportive policy frameworks, investment in participatory research, and stronger linkages between local practices and global sustainability agendas. By aligning ecological processes with socio-economic objectives, agroecology emerges as a transformative strategy for achieving multiple, interrelated SDGs.